Strengthening Civic Competences and State Defense of Children of Indonesia Migrant Workers in Sebatik, Indonesia-Malaysia Border - Wahyudi, Wahyudi; Huda, Mi'rojul; Krishnandya, Kharizha; Nuphanudin, Nuphanudin; Wasil, Mohammad; Usmi, Rianda; Gusti G. P, Esa Putra Bayu; Wahyuni, Jauhar; Lina, Hasna Nur; Zarkachi, Imam; Sitohang, Lidya Lestari (CV. Rayyan Dwi Bharata, 2024)
Indonesian citizens in the Sebatik Island area, the Indonesia-Malaysia border, have generally received their basic needs from Tawau, Malaysia, for a long time. This is indicated to have formed a dual nationalism mentality of Indonesian citizens in the region, which also affects some of the children of Indonesian migrant workers in Malaysia who live on Sebatik Island and place their national loyalty to those who benefit their lives. The purpose of this activity is to strengthen the values of nationalism and defend the country to the children of Indonesian migrant workers on Sebatik Island to face the decadence of nationalism and prevent foreign infiltration through the country's border areas. The method used in community service begins with analyzing the community situation, identifying problems, and determining specific work goals, problem-solving plans and social approaches. The result of this activity is the implementation of a program to strengthen nationalism and defend the country for the children of Indonesia migrant workers whose parents work in Malaysia through counselling and socialization with competent resource persons in their fields and a community of Sebatik Young citizens has been formed as a forum for self-actualization.